Reinventing the local scope of development: Participative shaping as an instrument for a sustainable spatial development in peri-urban regions - Buchecker, Matthias; Berz, Thomas (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
Involving the public in decision making is a common concern of policymakers and scientists. In the reality of planning praxis, however, the opposite tendency can be observed: the local residents increasingly withdraw from the local public life. Our investigations in two periurban communities show that this withdrawal is not primarily caused by the lack of suitable opportunities for the residents to participate in shaping the local public place. In order to revive public life and promote a need oriented community development, new informal instruments are needed for the residents to express their individual needs without jeopardising their social integration.